2020
DOI: 10.3390/pathogens9020111
|View full text |Cite
|
Sign up to set email alerts
|

Putative Role of a Yet Uncharacterized Protein Elicitor PeBb1 Derived from Beauveria bassiana ARSEF 2860 Strain against Myzus persicae (Homoptera: Aphididae) in Brassica rapa ssp. pekinensis

Abstract: This study reports the characterization of protein elicitor PeBb1 derived from entomopathogenic fungus Beauveria bassiana ARSEF-2860 strain and its putative role in induced systemic resistance in Brassica rapa ssp. pekinensis against green peach aphid Myzus persicae. The sequence of purified elicitor protein was matched with the genomic sequence of a hypothetical protein BBA_10269 from B. bassiana ARSEF-2860 (GenBank Accession No. XP_008603588.1). The protein-encoding gene PeBb1 contained 534 bp cDNA encoding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
(45 reference statements)
2
8
0
Order By: Relevance
“…These results validate the fact that herbivory by sap-sucking insects, for instance whiteflies, is more often manifested with enhanced expression levels of SA pathway-related genes [ 34 , 38 ]. Our results are in line with a recent study [ 50 ] that revealed important sub-lethal effects of the B. bassiana -derived PeBb1 protein elicitor on M. persicae on the plants of Brassica rapa concomitantly with the enhanced expression of JA and Et pathway-related genes.…”
Section: Discussionsupporting
confidence: 93%
“…These results validate the fact that herbivory by sap-sucking insects, for instance whiteflies, is more often manifested with enhanced expression levels of SA pathway-related genes [ 34 , 38 ]. Our results are in line with a recent study [ 50 ] that revealed important sub-lethal effects of the B. bassiana -derived PeBb1 protein elicitor on M. persicae on the plants of Brassica rapa concomitantly with the enhanced expression of JA and Et pathway-related genes.…”
Section: Discussionsupporting
confidence: 93%
“…naphthalene, with some plant compounds secreted via trichomes. Some of those plant compounds have been demonstrated to be potentially induced by endophytes, such as B. bassiana 55,56,59,69 . Furthermore, B. bassiana produces several anti‐insect or/and antimicrobial active metabolites that include tennelin, bassianin, pyridovericin, oosporein and pyridomacrolidin, 68,70 which might be also involved in the observed resistance against insects reported here.…”
Section: Discussionmentioning
confidence: 71%
“…Some of those plant compounds have been demonstrated to be potentially induced by endophytes, such as B. bassiana. 55,56,59,69 Furthermore, B. bassiana produces several anti-insect or/and antimicrobial active metabolites that include tennelin, bassianin, pyridovericin, oosporein and pyridomacrolidin, 68,70 which might be also involved in the observed resistance against insects reported here. All these possibilities could explain the distinctly increased resistance of B. bassiana-colonized tobacco seedlings against the aphids.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations